Prevalence and Characteristics of Pregnant Women Infected with Human Immunodeficiency Virus in Bamrasnaradura Hospital in 1987 – 1993 - Chaovavanich, Achara (Journal of Health Science of Thailand, 1994)
Prevalence of HIV infection and characteristic of pregnant women attending antenatal clinic of Bamrasnaradure Hospital in the period of 1989 – 1994 were analized. The prevalence of HIV was found to be gradually increasing from 0 to 0.13, 0.40, 0.94, 1.27.0.86 for the year 1989 10 1994 respectively. For those who with abortion, the prevalence was found to be 0.06,0.41,1.08,2.13,2.00 and 1.99 for 1989-1994 respectively. Majority of the HIV positive cases were housewives, contracted the virus sexually, and primigravid. Thirty percent of them had history of more than one sex partner. There were 79 of 198 cases whose husbands were tested of whom 72.15% were HIV positive. Recommendations of this study included: (1) more attention be paid on counseling services, especially for those still uninfected, (2) effective counseling services on family planning and contraception should be emphasized, and (3) obstetricians be able to manage HIV positive cases so as to reduce necessity for them to be referred to Bamrasnaradure Hospital.